Akuntabilitas Kinerja Satuan Polisi Pamong Praja di Kabupaten Sidenreng Rappang - Aan Priana Ransun (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
The purpose of this research was to determine how the Performance Accountability of Civil Service Police Unit in Sidenreng Rappang Regency along with all affecting factors. Data collection methods used in this research were (1) observation, (2) questionnaire, (3) interview, and (4) literature study. The collected data was analyzed using frequency tables and percentages. The population in this study were 187 people, and using the technique of random sampling that took as much as 15% of population. The results of the factors that influence the Performance Accountability of Civil Service Police Unit in Sidenreng Rappang Regency showed that the level of accuracy factor in carrying out their duties scored 52,77%, the professionalism in implementing a decision scored 55,52%, facilities and infrastructure to support tasks and functions score 44,44%, the clarity of rules against violators of regulations to support creating a safe and laws enforcement with scored 52,77%, and the level of discipline in carrying out their duties scored 36,11%.